Letters of gratitude: Improving well-being through expressive writing - Toepfer, Steven M.; Walker, Kathleen (Journal of Writing Research, 2009)
Researchers have shown that about 40% of our happiness is accounted for by intentional activity whereas 50% is explained by genetics and 10% by circumstances (Lyubomirsky, Sheldon & Schkade, 2005). Consequently, efforts to improve happiness might best be focused in the domain of intentional activity: willful and self-directed activity (Sheldon & Lyubomirsky, 2007). Such activity is nested in the "sustainable happiness model" proposed by Lyubomirsky, Sheldon, and Schkade (2005) which states that happiness is in part within our ability to manage. Earlier work (Fordyce, 1977; 1983) supports the premise that individuals can sustain levels of happiness through volitional behavior. The current pilot study explored one such intentional activity - composing letters of gratitude. It was hypothesized that writing three letters of gratitude over time would enhance important qualities of subjective well-being in the author; happiness, life-satisfaction, and gratitude.